Nusantara Aesthetics: The Beauty of Traditional Javanese Houses as A Foundation For Social Harmony and Respect - Sunarmi Sunarmi (Journal of Social Research, 2025)
This study seeks to find the concept of Nusantara Aesthetics in Javanese traditional houses, its correlation with the value of the Javanese people. The research is positioned in a critical thinking system, using the semiotic critical theory of visual communication. The location of the research is in Java. The study uses qualitative methods and interpretive analysis techniques that use a qualitative approach. Broadly speaking, the findings in the study are that the concept of Nusantara Aesthetics found in Javanese Traditional Houses is realized to maintain harmony. Harmony in social life can be achieved with the pillars including attitudes: aruh, gupuh, lungguh, and suruh. Aruh is a grapyak or friendly attitude to maintain safety and harmony with the environment. The representation of the attitude of the Aruh is that the Javanese traditional house has a Regol which is located at the front as a barrier with a road in the form of a small open house. Gupuh is an age-age attitude, Javanese people respect guests with an age-age attitude when they come out of the house to welcome guests in masks. The mask of the front building in the configuration of the Javanese house as a face, making the shade house a representation of the value of shade in accepting the presence of people. Lungguh is sitting, Javanese people receive guests to talk about something by sitting, therefore the house has a pendapa in the form of a spacious open house, a representation of a loose heart/freely accepting the presence of people.